Characterization of EO-1 Strains (Pseudomonas kingii) Isolated from Clinical Specimens and the Hospital Environment - Gilardi, G. L. (1970)
Ten strains of the pseudomonad designated EO-1 and named Pseudomonas kingii, which were isolated from clinical specimens and the hospital environment, are described.